Accessible Package of Services in Health Insurance Reform in Albania - Sinaj, Zamira; Dumi, Alba; Bodo, Eliza (Mediterranean Journal of Social Sciences, 2012)
This article presents a summary of the current status, of health Albanian system.The developing health care system ofundergraduate, postgraduate and continuous medical education in Albania and suggests opportunities for development andpartnerships that would help the country's medical education reform. The impact of these changes and developing health caresector may be reduced by two modifications in undergraduate medical programs. First identifying, training practicediscrepancies, with a view of correcting them. Computerization of all pharmacies started for the first time in 2007. Partnershipwith health institutions and namely with pharmacies was also strengthened. The intention of this corporation was to insurehardware equipment to support the software produced by HII.Since their system was designed in such a way that it served notonly to HII, but also to pharmacies in their everybody work, very soon pharmacists that previously didn’t want to procureequipment became our collaborators in improving the system. The HII received more than 17% of all health funds, with 8.5%coming from the state budget, 4.3% from employers and 4.4% from individual contributions. While the state remains the majorsource of health care financing, its contribution shrank from around 84% in 1990 to less than 60% in 1999 as other funding,especially out-of-pocket payments, increased.